Novel insights into sex-specific differences in heart rate variability and autonomic nervous system regulation during spawning behavior in chum salmon (Oncorhynchus keta) revealed by re-analysis of ECG logger data - Makiguchi, Yuya; Abe, Takaaki K.; Ichimura, Masaki (Frontiers in Physiology, 2025)
This study reanalysed electrocardiogram (ECG) data collected in a previous study on chum salmon to explore sex-specific differences in heart rate variability (HRV) and autonomic nervous system regulation during spawning. The prior research included six female and five male salmon with implanted ECG loggers, observed during spawning, and ten additional females for pharmacological experiments on autonomic nervous system effects. The analysis uncovered distinct HRV patterns between sexes. Females exhibited an increase in heart rate from 82.27 to 86.16 bpm post-spawning, while males decreased from 74.71 to 67.78 bpm. Breakpoint analysis identified four change points in female HRV and five in male HRV. Females displayed a heart rate decrease 21 min before spawning, while males maintained stable rates until spawning. Both sexes experienced cardiac arrest at spawning, consistent with the previous study. HRV changes did not always correspond directly with spawning behaviors, indicating autonomic nervous system involvement beyond physical exertion. Pharmacological experiments showed that atropine, a parasympathetic blocker, suppressed HRV and prevented cardiac arrest, emphasizing the key role of the parasympathetic system in regulating spawning-related HRV. The study suggests that HRV during salmon spawning is regulated by physical activity and autonomic nervous system control, with an important role in parasympathetic activation. This activation begins 20 min before spawning in females, serving as a preparatory mechanism for the physiological demands of spawning. These findings improve our understanding of salmonid reproductive physiology and may inform conservation strategies. Future research should investigate direct measurements of autonomic activity, environmental influences on HRV, and the relationship between HRV patterns and reproductive success. Combining HRV data with other physiological measurements could offer a more comprehensive understanding of the regulatory mechanisms underlying spawning behavior and the energetic costs associated with reproduction in salmonids.